Animal performance of indigenous Red Chittagong cattle in Bangladesh - Sharmin Nahar; Abul Fazal Mohammad Fayjul Islam; Mohammad Azharul Hoque; Abul Kashem Fazlul Haque Bhuiyan (Acta Scientiarum. Animal Sciences, 2016)
The study was carried out using body weights at several ages of Red Chittagong cattle performed on two management systems viz in-farm and  in-field. There were a total of 208 animals whose body weights were recorded from 2005 to 2013. The overall average weight at birth (BW), 3-month (3MWT), 6-month (6MWT), 9-month (9MWT), 12-month (12MWT), 15-month (15MWT), 18-month (18MWT), 21-month (21MWT), 24-month (24MWT), 27-month (27MWT), 30-month (30MWT) and 33-month (33MWT) were 15.4 ± 0.15, 30.5 ± 0.75, 43.1 ± 1.03,54.6 ± 1.77,65.7 ± 2.34,70.7 ± 2.72,86.7 ± 4.33,92.1 ± 3.71,105.2 ± 4.43,114.5 ± 5.04,122.8 ± 4.71 and 101.8 ± 12.16 kg, respectively in farm condition while corresponding values field condition were 14.7 ± 0.24, 31.1 ± 0.53, 41.9 ± 0.78, 52.2 ± 0.98, 60.99 ± 1.12, 70.6 ± 1.66, 79.5 ± 2.04,89.2 ± 2.61, 102.1 ± 4.01,112.3 ± 3.81, 128.4 ± 5.63 and 100.7 ± 21.53 kg respectively. The effect of different non genetics factors such as management system, sex, parity of dam, season of birth and year of birth were estimated on body weight. Linear growth curves from birth to 33 months of age of RCC on two management systems showed an increasing trend in body weight from birth to 30 months of age with highest body weight attained at 30 months of age and afterwards showed a gradual declining trend. The results indicated that RCC has almost similar body weight and growth performance in farm and field conditions meaning their equal suitability in both management systems.